Factors Influencing Consumer Decisions In Purchasing At Woci Kitchens In Kepahiang Regency - Lestari, Ayuni Wulan; Irwanto , Tito; Yustanti , Nirta Vera (Journal of Management, Economic, and Accounting, 2024)
The purpose of this study is to find out what factors influence consumer decisions in purchasing at Woci kitchens in Kepahiang district. The sample in this study was 100 customers who shopped at Dapur Woci in Kepahiang. Data collection using questionnaires and the analysis methods used are multiple linear regression, determination test and hypothesis test. The results of the multiple linear regression equation show the equation Y = 5.139 + (-0.208) X1 + (-0.715) X2 + 0.926 X3 + 0.934 X4 meaning that if social, personal, psychological factors increase, consumer decisions in purchasing will also increase. Cultural factors are not significant to consumer decisions in purchasing at Dapur Woci, this can be seen with a significant value of 0.334 greater than 0.05. Social factors have a significant influence on purchasing decisions in the Woci Kitchen, this is evidenced by a value of 0.024 smaller than 0.05. Personal factors have a significant influence on consumer decisions in purchasing at Dapur Woci in Kepahiang. This is evidenced by a significant value of 0.011 smaller than 0.05. Psychological factors have a significant influence on consumer decisions in purchasing at Dapur Woci in Kepahiang, this is evidenced by a significant value of 0.001 smaller than 0.05. It can be concluded that only social factors and personal factors, psychological factors that are significant to consumer decisions in purchasing At Dapur Woci in Kepahiang this is evidenced by a significant value of 0.000 smaller than 0.05.